ACHIEVING THE DESIRED LEVEL OF AGRESSIVENESS AND FOCUS IN DEFENSE - Dzikic, Aleksandar; Hihajlovic, Filip (Sport- és Egészségtudományi füzetek, 2025)
There is a firm belief that there is not one right way we should do things, because there are different teams, differ-ent players and different clubs. Defense is still a very essen-tial part of winning, some teams are made to outscore the opponent, but at the end of the season, you can’t rely on this. In this topic rules are very important too, believing in concepts, working on them, so they become habits. Good defensive teams are not built to outscore, they are built to play organized.